A Digital World, Unlimited Abilities: The Role of Technology in Unleashing the Skills of Students with Special Needs - HANNACHI, NADJIM (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2025)
This research explores the pivotal role of digital Tools in enhancing education for students with special needs, aiming to bridge the educational gap and foster a more equitable and inclusive Learning environment. In an increasingly technology-dependent world, it is imperative to ensure That all students, regardless of their Abilities, benefit from these powerful Tools. The Study highlights a diverse range of technologies, such as tablets, Virtual reality (VR), and Specialized educational software, examining how they contribute to improving Learning experiences for students with special needs. For instance, tablets can provide an interactive platform for self-Directed Learning, while VR offers immersive and engaging educational experiences. The research is grounded in Learning theories and effective teaching practices to understand how technology can be tailored to meet the individual needs of students with special needs. By integrating these theories with technology, customized Learning experiences can be designed to address the unique requirements of each student. The central issue revolves around leveraging digital technology as a Catalyst to enhance Learning and un lock the potential of students with special needs. Findings reveal That digital Tools can create an interactive and flexible Learning environment, adaptable to individual student needs. They enable Personalized Learning paces, differentiates content delivery, and active engagement. The Study also provides in-depth insights into promising practices in technology-Assisted special education. These include the use of individualized Learning applications, Augmented and alternative communication Tools, and adaptive Learning platforms.